2016
DOI: 10.1111/jnc.13552
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal filopodium formation induced by the membrane glycoprotein M6a (Gpm6a) is facilitated by coronin‐1a, Rac1, and p21‐activated kinase 1 (Pak1)

Abstract: Stress-responsive neuronal membrane glycoprotein M6a (Gpm6a) functions in neurite extension, filopodium and spine formation and synaptogenesis. The mechanisms of Gpm6a action in these processes are incompletely understood. Previously, we identified the actin regulator coronin-1a (Coro1a) as a putative Gpm6a interacting partner. Here, we used co-immunoprecipitation assays with the anti-Coro1a antibody to show that Coro1a associates with Gpm6a in rat hippocampal neurons. By immunofluorescence microscopy, we demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…Two other genes that definitely need further characterization are GPM6A (the highest positive fold of change on RNA-seq) and PCDH18 (the highest association with TVDT). GPM6A is highly expressed in brain tissue and is involved in neuronal differentiation, including differentiation and migration of neuronal stem cells, neuronal plasticity and filopodia outgrowth and motility and probably synapse formation (42). PCDH18 belongs to the protocadherin gene family and is thought to play a role in the establishment and function of specific cell-cell connections in the brain (43).…”
Section: Discussionmentioning
confidence: 99%
“…Two other genes that definitely need further characterization are GPM6A (the highest positive fold of change on RNA-seq) and PCDH18 (the highest association with TVDT). GPM6A is highly expressed in brain tissue and is involved in neuronal differentiation, including differentiation and migration of neuronal stem cells, neuronal plasticity and filopodia outgrowth and motility and probably synapse formation (42). PCDH18 belongs to the protocadherin gene family and is thought to play a role in the establishment and function of specific cell-cell connections in the brain (43).…”
Section: Discussionmentioning
confidence: 99%
“…Each experiment was scored blind. Previously we have shown that all filopodial protrusions induced by Gpm6a overexpression are labeled by phalloidin ( Alvarez Julia et al, 2016 ) and that quantification of phalloidin-labeled filopodia coincided with quantification when EGFP is used to detect filopodia in transfected neurons ( Alvarez Julia et al, 2016 ).…”
Section: Methodsmentioning
confidence: 87%
“…Dissociated neuronal cultures were prepared from hippocampi of embryonic day 19 Sprague–Dawley rats obtained from the Faculty of Veterinary Sciences (Buenos Aires, Argentina), as described previously ( Alvarez Julia et al, 2016 ). Briefly, hippocampal tissue was treated with 0.25% (wt/vol) trypsin in HBSGK buffer (4.8 g/l HEPES, 8.7 g/l NaCl, 0.22 g/l KCl, 0.36 g/l glucose, pH 7.4) for 15 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations